Observed Emergence of the Climate Change Signal: From the Familiar to the Unknown. Issue 6 (17th March 2020) - Hawkins, E.; Frame, D.; Harrington, L.; Joshi, M.; King, A.; Rojas, M.; Sutton, R.
Abstract: Changes in climate are usually considered in terms of trends or differences over time. However, for many impacts requiring adaptation, it is the amplitude of the change relative to the local amplitude of climate variability which is more relevant. Here, we develop the concept of "signal‐to‐noise" in observations of local temperature, highlighting that many regions are already experiencing a climate which would be "unknown" by late 19th century standards. The emergence of observed temperature changes over both land and ocean is clearest in tropical regions, in contrast to the regions of largest change which are in the northern extratropics—broadly consistent with climate model simulations. Significant increases and decreases in rainfall have also already emerged in different regions with the United Kingdom experiencing a shift toward more extreme rainfall events, a signal which is emerging more clearly in some places than the changes in mean rainfall. Plain Language Summary: Changes in climate are translated into impacts on society not just though the amount of change, but how this change compares to the variations in climate that society is used to. Here we demonstrate that significant changes, when compared to the size of past variations, are present in both temperature and rainfall observations over many parts of the world. Key Points: The signal of changes in observed temperature and rainfall due to global warming has clearly emerged in many regions and at mesoscales Tropical regions have experienced the largest changes in temperature relative to the amplitude of internal variability Signals of increasing extreme rainfall are emerging more quickly than signals in mean rainfall over many parts of the United Kingdom